Project management practice in interreg projects: Reflective analysis and recommendations - Susanne Marx (Hochschule Stralsund, Stralsund Information Management Team (SIMAT), 2017)
Drawing on experiences of the author in Interreg co-operation projects, this paper relates project management practice in two case study projects to selected key topics of project management theory, resulting into a series of recommendations primarily based on personal reflection. The case study projects were both funded by the South Baltic Cross-border Co-operation Programme 2007 - 2013. This paper presents the strategic environment of the case study projects. The framework of public requirements, the geographic distribution of the project team and the concept of a multi-organisational project set-up, lead to increased complexity. In assessing this specific project environment, the paper evaluates the relative importance of the project management knowledge areas of the PMBOK® and in doing so, putting a focus on project sustainability management as a significant area for further efforts towards enhancing project management standards and indeed, long-term project success. The balanced matrix of the multi-organisational structure required management awareness of the lead partner for enacting non-formal authority and empowerment, resulting in the importance of building trust. Since stakeholder influence and needs were critical for project success, this paper presents a process for analyzing stakeholders to prioritize and develop individual strategies. The concept of the project lifecycle is established in the PM standards of the PMI® and APM. In transferring these standard project lifecycles to the considered Interreg-projects, a major distinction noted, is the timespan between an application for funding and (in case of success) the start of project implementation. This period can take several months, in which the project risks to lose momentum. Another critical, yet largely neglected phase is after the project closure, a time when promised benefits for stakeholders potentially materialize. This paper recommends strengthening the role of the 'program' in terms of project management qualification, continuous improvement and cross-project learning. Finally, the project management maturity is assessed, recommending the following areas for further development: Benefit, Stake-holder and Risk Management.
Keywords: 650